Evaluasi Pembelajaran Pendidikan Agama Islam di Lembaga Kesejhateraan Sosial Anak Yatim Putri ‘Aisyiyah Karanganyar - Supatmi, Supatmi; Ridoh, Rasyid (TSAQOFAH, 2024)
The evaluation of learning plays a strategic role in maintaining quality education. Learning and Care Centers can serve as a primary alternative in the development of values and character of students through an integrated Islamic Religious Education (Pendidikan Agama Islam) learning approach combined with a comprehensive learning evaluation system. This research aims to understand the methods of Islamic Religious Education learning at the Orphanage 'Aisyiyah Karanganyar. The research methodology employs a qualitative-descriptive approach with field research. The research findings indicate that the Islamic Religious Education learning methods at the 'Aisyiyah Karanganyar Orphanage are effective, as evidenced by the practical application of Islamic Religious Education learning by the foster children regarding "maeri" (moral education) conveyed by the educators (musyrifah). Learning.